2009
DOI: 10.1002/bmc.1219
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of five coumarins in Angelicae dahuricae Radix by HPLC/UV and LC‐ESI‐MS/MS

Abstract: Rapid, simple and reliable HPLC/UV and LC-ESI-MS/MS methods for the simultaneous determination of five active coumarins of Angelicae dahuricae Radix, byakangelicol (1), oxypeucedanin (2), imperatorin (3), phellopterin (4) and isoimperatorin (5) were developed and validated. The separation condition for HPLC/UV was optimized using a Develosil RPAQUEOUS C(30) column using 70% acetonitrile in water as the mobile phase. This HPLC/UV method was successful for providing the baseline separation of the five coumarins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…Several methods have been developed using various chromatographic and spectroscopic tools, mostly high‐performance liquid chromatography (HPLC) and HPLC‐mass spectrometry (MS), for the identification of the botanical origin and/or major constituents in Apiaceae medicinal plants . However, these methods are not efficient for the analysis of large numbers of samples because of the time‐consuming sample preparation steps involved, such as extraction and solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed using various chromatographic and spectroscopic tools, mostly high‐performance liquid chromatography (HPLC) and HPLC‐mass spectrometry (MS), for the identification of the botanical origin and/or major constituents in Apiaceae medicinal plants . However, these methods are not efficient for the analysis of large numbers of samples because of the time‐consuming sample preparation steps involved, such as extraction and solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al reported on LC-MS analysis for five furocoumarins in A. dahuricae [196]. Byakangelicol, oxypeucedanin, imperatorin, phellopterin and isoimperatorin were determined within 5.5 min with gabapentin as the internal standard using QqQ mass spectrometer in MRM mode.…”
Section: Coumarinsmentioning
confidence: 99%
“…Cnidilin (9-methoxy-4-((3-methylbut-2-en-1-yl)oxy)-7H-furo [3,2-g]chromen-7-one), one of coumarin compounds, represents a major active constituent of Radix Angelicae dahuricae [2,3]. However, there were only a few related studies in vitro research, which contained simultaneous determination of coumarins in Qingxuan Tablets [4], quantitative determination of Radix Angelicae dahuricae (Liquid Chromatography [5], High Liquid Chromatography Mass Spectrometry [5,6], Capillary Electrophoresis [7]), identification of the component [8].…”
Section: Introductionmentioning
confidence: 99%